Testing and analysis on nonlinear creep behaviour of concrete-filled steel tubes with circular cross-section. (15th April 2019) - Wang, Yu Yin; Geng, Yue; Chen, Jie; Zhao, Mu Zi
Highlights: Non-linear creep tests on circular CFST stubs. Variation of confinement effects with time for CFST under sustained loading. Numerical modelling for non-linear creep of circular CFST stubs with the consideration of confinement effects. Abstract: Owing to the excellent seismic resistance of circular concrete-filled steel tubes (CFST), no specific limitation on their in-service axial load level is provided in Chinese codes. Therefore, nonlinear creep could occur in Chinese CFST applications. This study intends to experimentally investigate the nonlinear creep behaviour and the creep failure behaviour of CFST columns. Fourteen specimens were subjected to sustained loading for 200–500 days. The sustained loading level ranged between 40% and 80% of the cross-sectional strength of the specimens. The strain state of steel tubes was monitored to determine how the confinement effects vary with time. Ultimate loading tests were finally conducted on all specimens immediately after the long-term tests to investigate the nonlinear creep effects on the cross-sectional capacity and ductility of the CFST specimens. A method was then proposed for the nonlinear creep analysis of circular CFST members with consideration of the beneficial contribution of confinement effects. Existing nonlinear models were benchmarked against available experimental results to evaluate their adequacy in predicting the nonlinear creep responses of CFST members. Experimental results indicated that nonlinear creep could lead to a 58–200% increase in the creep coefficient, in which case the linear creep model will underestimate the long-term deformation by 37–67%. Owing to the vertical stress redistribution between the concrete core and the steel tube and the confinement effects, no creep failure occurred during the 500-day tests, and the nonlinear creep barely influenced the cross-sectional capacity of the specimens. A model was recommended to predict the nonlinear creep deformation of CFST members.